Elachista : la dottrina dei minimi nell'epicureismo : with English summary - Verde, Francesco (Ancient and medieval philosophy., 2013)
The first monograph entirely devoted to the Epicurean doctrine of minimal parts. The Epicurean doctrine of minimal parts (ta elachista) is a crucial aspect of Epicurus''s philosophy and a genuine turning point compared to the ancient atomism of Leucippus and Democritus. This book consists of three chapters: a philological and theoretical analysis of the primary sources (Epicurus and Lucretius) of the doctrine, a reconstruction of its likely historical background (Xenocrates, Aristotle, Diodorus Cronus), and a close examination of the chiefly geometrical development of this theory within the phi.